Integrating Islamic Character Values for Competitive Human Resource Development in Educational Institutions - Atina Balqis Azzahra; Imam Junaris; Achmad Naufal Rozaan (The Faculty of Education and Teaching Training, 2026)
The development of superior human resources imbued with Islamic character has become a strategic issue for strengthening the competitiveness of educational institutions in the era of globalization. This study aims to analyze the concept, role, and strategy of developing superior human resources grounded in Islamic values within educational institutions. This research employed a qualitative approach, using library research methods, to examine scientific literature on human resource management, Islamic character education, and institutional competitiveness. Data were collected through documentation techniques and analyzed using descriptive qualitative analysis. The findings reveal that superior human resources with Islamic character are characterized by professionalism, functional competence, participatory excellence, collaboration, and spiritual moral integrity. Islamic character values, such as honesty, trustworthiness, discipline, responsibility, and social concern, play an important role in strengthening professionalism, organizational culture, and institutional credibility. Furthermore, the study identifies several strategic approaches to developing Islamic-character-based human resources, including value-based recruitment, continuous character training, ethical performance evaluation, and the establishment of a Qur’anic organizational culture. This study contributes theoretically to the development of Islamic human resource management concepts by integrating professional, moral, and spiritual dimensions into human resource development. In practice, the findings may serve as a reference for educational institutions in formulating sustainable strategies to improve institutional competitiveness through Islamic character-based human resource development.